L'appel de Calcutta : continuités, ruptures et réappropriations chez les expatriés humanitaires en Inde - Giguère, Nadia (Anthropologica, 2022)
Through the accounts of humanitarian workers in Calcutta who chose expatriation, we shall explore how repre- sentations of the self and of the other are transformed through the experience of volunteering and by borrowing from history and fantasy. While classical representations dating back to the colonial period and the development of volunteer tourism keep modeling the Western experience, we also note that experiences of emancipation and a new sense of belonging support together the expatriation project. Meanwhile, transnational practices reinforce feelings of alienation towards Western lifestyles. The article suggests that the expatriates' liminal status allows social disjuncture as well as historical reproduction of the relation- ship to the other.